Blake 2.0
XIII, 309 p.
Keywords: Blake said of his works, 'Tho' I call them Mine I know they are not Mine'. So who owns Blake? Blake has always been more than words on a page. This volume takes Blake 2.0 as an interactive concept, examining digital dissemination of his works and reinvention by artists, writers, musicians, and filmmakers across a variety of twentieth-century media.